US Table Tennis (2008)
USA Table Tennis is the national governing body for the Olympic sport of table tennis in the United States. For the 2008 Olympic Games we project to qualify 4 athletes from which, at least one junior. The way we believe we can improve our performance in the next and future games, it is well reflected in our Strategic Developmental Plan. Some of the most important ways to improve our performance are: - Opening and utilizing training centers. - Joint training camp with the best team in the worlds. - Improving the level of our coaches. - Having a year round program for National Teams. USATT is planning to prepare the new generation of young athletes to improve and develop so they can reach a high international level. In the years to come we expect the young players to become the National Team members and achieve good international results and by 2012-2016 they will be able to become Olympic medalists. USATT set milestones and goals for each year starting 2005 all the way to 2016. The goals and milestones are set over a long period of time and changes in the milestones and goals in the programs are expected. Changes could occur due to different reasons as: - ITTF rules change. - Social environment. - Economic influence. - Unexpected issues. We are aware that some of the milestones set for the upcoming years might not be met, but this will not change the ultimate goal: medaling in the Olympic Games.